Genome-wide characterization and functional identification of MYB genes in Malus sieversii infected by Valsa mali - Ding, Yu; Yang, Qihang; Waheed, Abdul; Zhao, Mingqi; Liu, Xiaojie; Kahar, Gulnaz; Haxim, Yakupjan; Wen, Xuejing; Zhang, Daoyuan (Frontiers in Plant Science, 2023)
Among the most important transcription factors in plants, MYB (v-myb avian myeloblastosis viral oncogene homolog) regulates the expression network of response genes in response to a variety of stresses such as fungal infection. In China, the canker disease Valsa mali threatens the survival of Malus sieversii, an ancestor of the cultivated apple. Using the M. sieversii genome, we identified 457 MsMYB and 128 R2R3-MsMYB genes randomly distributed across 17 chromosomes. Based on protein sequence and structure, R2R3-MsMYBs were phylogenetically divided into 29 categories and 26 conserved motifs were identified. We further predicted cis-elements on the 2000kb promoter region of R2R3-MsMYBs based on the genome. During V. mali infection, M. sieversii transcriptome analysis showed 27 R2R3-MsMYBs were significantly differentially expressed indicateing R2R3-MsMYBs playing a key role to response V. mali infection. With transient transformation, MsMYB14, MsMYB24, MsMYB39, MsMYB78, and MsMYB108, which were strongly induced by V. mali infection, were identified functionally. Among the five MsMYBs, MsMYB14 and MsMYB78 were both important in enhancing resistance to diseases, while MsMYB24 inhibited resistance. We gain a better understanding of the MsMYB transcription factor family and have laid the foundation for a future research program on disease prevention strategies in M. sieversii based on the results of this study.